Nitrogen back-diffusion during multiple-breath washout with 100% oxygen. Issue 3 (9th September 2017) - Sullivan, Leanna; Forno, Erick; Pedersen, Knud; Nielsen, Jørgen G.; Weiner, Daniel J.
The lung clearance index (LCI) measured by multiple-breath washout (MBW) is defined as the number of lung volume turnovers needed to reduce the concentration of a blood-insoluble tracer gas by a factor of 40 during tidal breathing [1]. Over the past two decades, the MBW test has proven to be particularly useful in cystic fibrosis, and studies [2, 3] have demonstrated its superior sensitivity to that of forced expiratory volume in 1 s (FEV1 ). The ideal tracer gas for the LCI test is so insoluble in blood that any gas exchange effects are insignificant, and it can be measured in concentrations low enough that the tracer itself does not affect the physical properties of the respired air or gas mix. Historically, SF6 is the tracer gas that is most often used in the implementation of the MBW test [1]. However, it has been suggested that the LCI can instead be derived from the washout of nitrogen resident in the lungs using 100% oxygen, and this approach is being applied in a number of ongoing clinical trials. Nitrogen diffuses from blood into lung during nitrogen washout which can affect multiple breath washout results http://ow.ly/9dcy30dOuwZ